2018
DOI: 10.1038/s41598-018-22913-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of NF-E2 Related Factor 2 (Nrf2) and inflammatory cytokines in recent onset Type 2 Diabetes Mellitus

Abstract: We investigated the association of redox regulator Nuclear factor erythroid 2-related factor 2 (Nrf2) and inflammatory cytokines as well as clinical remission in patients with recent onset type 2 diabetes (DM). Blood was collected from 180 DM patients (105 males/75 females) and 150 control subjects (86 males/64 females). Blood glucose, HbA1c, lipid profile and Nrf2 levels were determined along with circulatory cytokines in study subjects. The data were adjusted with confounding factors such as age and sex usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 45 publications
(64 reference statements)
6
61
2
Order By: Relevance
“…In contrast, polarization of anti-inflammatory Th2 cells was decreased [ 15 20 ]. A recent study [ 21 ] showed that Th1/Th2 ratio and levels of cytokines (e.g., IL-4, IL-10, IL-13, and IFN- γ ) were significantly elevated, whereas nuclear factor erythroid 2-related factor 2 (Nrf2) and its downstream targets, which act with antioxidant, detoxification, and maintenance of cellular redox homeostasis and glutathione homeostasis and influence mitochondrial biogenesis, were decreased in T2DM patients. The circulatory levels of Nrf2 showed a positive correlation with the levels of Th2 cytokines and negative correlation with the levels of Th1 cytokines [ 21 ].…”
Section: T Cells In T2dmmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, polarization of anti-inflammatory Th2 cells was decreased [ 15 20 ]. A recent study [ 21 ] showed that Th1/Th2 ratio and levels of cytokines (e.g., IL-4, IL-10, IL-13, and IFN- γ ) were significantly elevated, whereas nuclear factor erythroid 2-related factor 2 (Nrf2) and its downstream targets, which act with antioxidant, detoxification, and maintenance of cellular redox homeostasis and glutathione homeostasis and influence mitochondrial biogenesis, were decreased in T2DM patients. The circulatory levels of Nrf2 showed a positive correlation with the levels of Th2 cytokines and negative correlation with the levels of Th1 cytokines [ 21 ].…”
Section: T Cells In T2dmmentioning
confidence: 99%
“…A recent study [ 21 ] showed that Th1/Th2 ratio and levels of cytokines (e.g., IL-4, IL-10, IL-13, and IFN- γ ) were significantly elevated, whereas nuclear factor erythroid 2-related factor 2 (Nrf2) and its downstream targets, which act with antioxidant, detoxification, and maintenance of cellular redox homeostasis and glutathione homeostasis and influence mitochondrial biogenesis, were decreased in T2DM patients. The circulatory levels of Nrf2 showed a positive correlation with the levels of Th2 cytokines and negative correlation with the levels of Th1 cytokines [ 21 ]. In addition, it showed that CD4+ and CD8+ T cells were infiltrated in both visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT), with proinflammatory Th1 and Th17 cells significantly more frequent in VAT as compared with SAT.…”
Section: T Cells In T2dmmentioning
confidence: 99%
“…Some health-promoting compounds, like betanin, can interfere in the activation of transcriptional factors, i.e. the nuclear factor kappa B (NF-kB) and the factor 2 related to nuclear erythroid factor 2 (Nrf2), master regulators in homeostasis redox, which coordinate the RNA synthesis of numerous genes involved in inflammatory, cytoprotective and antioxidant responses (Siti, Kamisah, and Kamsiah 2015;Lingappan 2018;Liu et al 2019;Baird and Yamamoto 2020;Sireesh et al 2018;Sies, Berndt, and Jones 2017).…”
Section: Betanin Atherogenesis and Cardiovascular Diseasesmentioning
confidence: 99%
“…Furthermore, it has been reported that interaction between Kelch-like ECH-associated protein 1 (Keap1) and nuclear factor erythroid 2-related factor 2 (Nrf2) can increase anti-inflammatory effects 8 . Previous reports have also reported that diabetes-induced inflammation and oxidative stress could induce intrinsic antioxidant response through the Keap1/Nrf2 pathway 9,10 . Incretin-related drugs decreased inflammatory status and enhanced Nrf2 system in DKD 11 .…”
mentioning
confidence: 92%